Chemically chargeable photo battery - Thimmappa, Ravikumar; Paswan, Bhuneshwar; Gaikwad, Pramod; Devendrachari, Mruthyunjayachari Chattanahalli; Kotresh, Harish Makri Nimbegondi; Mohan, Ramsundar Rani; Alias, Joy Pattayil; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry C, 2015)
Here we show a surrogate strategy for power production, wherein light is used to actuate a discharge Chemistry in the cathode of an aqueous rechargeable battery (ARB). The proposed photo battery consists of a titaninm nitride photoanode, promising. cathode:material iron(III) hexacyanoferrate(II) as the battery active species, and Na2S2O8 as the chemical charging agent The photo battery delivered negligible capacity in the dark and the capacity shot up to 77.8 mAh/g when artificially shined light, confirming that the battery chemistry is light driven. In the ambient light, the device retained 72% of its artificial light discharge capacity with a stable cycling for more than 100 cycles. Further, an unprecedented means for charging the battery rapidly is presented using Na2S2O8 and it revitalized the battery in 30 s without any external bias. This methodology of expending a photoanode extends to a battery that is free from dissolution of active materials, irreversible structural changes, spontaneous deinsertion reactions, and safety concerns commonly encountered in the state of the art anode materials in ARBs. Apart from bringing out a sustainable way for power production, this device opens up avenues for charging the battery in the likely events of electrical input unavailability, while solving the critcial issues of longer charging time and higher charging voltage.

Unprecedented isomerism-activity relation in molecular electrocatalysis - Kottaichamy, Alagar Raja; Begum, Shabbah; Nazrulla, Mohammed Azeezulla; Dargily, Neethu Christudas; Devendrachari, Mruthyunjayachari Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2020)
The role of electrocatalysts in energy storage/conversion, biomedical and environmental sectors, green chemistry, and much more has generated enormous interest in comprehending their structure-activity relations. While targeting the surface-to-volume ratio, exposing reactive crystal planes and interfacial modifications are time-tested considerations for activating metallic catalysts; it is primarily by substitution in molecular electrocatalysts. This account draws the distinction between a substituent's chemical identity and isomerism, when regioisomerism of the -NO2 substituent is conferred at the ``alpha'' and ``beta'' positions on the macrocycle of cobalt phthalocyanines. Spectroscopic analysis and theoretical calculations establish that the beta isomer accumulates catalytically active intermediates via a cumulative influence of inductive and resonance effects. However, the field effect in the alpha isomer restricts this activation due to a vanishing resonance effect. The demonstration of the distinct role of isomerism in substituted molecular electrocatalysts for reactions ranging from energy conversion to biosensing highlights that isomerism of the substituents makes an independent contribution to electrocatalysis over its chemical identity.

Regio-isomerism directed electrocatalysis for energy efficient zinc-air battery - Mukhopadhyay, Sanchayita; Devendrachari, Mruthyunjayachari Chattanahalli; Kanade, Sandeep C.; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Thotiyl, Musthafa Ottakam (iScience, 2022)
We have investigated the role of ligand isomerism in modulating the mechanisms and kinetics associated with charge/ discharge chemistry of an aqueous metal-air battery. The dominant electron-withdrawing inductive effect (-I effect) and the diminished electron-withdrawing resonance effect (-R effect) in the alpha-NO2 isomer noticeably diminishes the rate of oxygen reduction (ORR) and oxygen evolution reactions (OER) on the catalytic Co-center. In their beta-counterpart, the cumulative -I and -R effects noticeably enhance the OER and ORR kinetics on the same catalytic Co-center. Therefore, the regioisomerism of the -NO2 functionality amplifies the kinetics of ORR/OER without influencing their mechanistic pathways. When isomeric electrocatalysts are integrated to aid the charge chemistry of a Zn-air battery, the overpotential could be decreased by similar to 250mV with beta-NO2 isomer leading to a round-trip efficiency as high as 60%. This work contributes to the design of novel molecular platforms to target the overall round-trip efficiency of energy storage and conversion devices.

Unprecedented energy storage in metal-organic complexes via constitutional isomerism - Kottaichamy, Alagar Raja; Deebansok, Siraprapha; Deng, Jie; Nazrulla, Mohammed Azeezulla; Zhu, Yachao; Bhat, Zahid Manzoor; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Fontaine, Olivier; Thotiyl, Musthafa Ottakam (Chemical Science, 2023)
The essence of any electrochemical system is engraved in its electrical double layer (EDL), and we report its unprecedented reorganization by the structural isomerism of molecules, with a direct consequence on their energy storage capability. Electrochemical and spectroscopic analyses in combination with computational and modelling studies demonstrate that an attractive field-effect due to the molecule's structural-isomerism, in contrast to a repulsive field-effect, spatially screens the ion-ion coulombic repulsions in the EDL and reconfigures the local density of anions. In a laboratory-level prototype supercapacitor, those with beta-structural isomerism exhibit nearly 6-times elevated energy storage compared to the state-of-the-art electrodes, by delivering similar to 535 F g(-1) at 1 A g(-1) while maintaining high performance metrics even at a rate as high as 50 A g(-1). The elucidation of the decisive role of structural isomerism in reconfiguring the electrified interface represents a major step forward in understanding the electrodics of molecular platforms.

Electrochemical energy storage in an organic supercapacitor via a non-electrochemical proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Devendrachari, Mruthyunjayachari Chattanahalli; Mendhe, Rahul Mahadeo; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Chemical Science, 2024)
Contrary to conventional beliefs, we show how a functional ligand that does not exhibit any redox activity elevates the charge storage capability of an electric double layer via a proton charge assembly. Compared to an unsubstituted ligand, a non-redox active carboxy ligand demonstrated nearly a 4-fold increase in charge storage, impressive capacitive retention even at a rate of 900C, and approximately a 2-fold decrease in leakage currents with an enhancement in energy density up to approximately 70% via a non-electrochemical route of proton charge assembly. Generalizability of these findings is presented with various non-redox active functional units that can undergo proton charge assembly in the ligand. This demonstration of non-redox active functional units enriching supercapacitive charge storage via proton charge assembly contributes to the rational design of ligands for energy storage applications.

Ligand isomerization driven electrocatalytic switching - Kottaichamy, Alagar Raja; Nazrulla, Mohammed Azeezulla; Parmar, Muskan; Thimmappa, Ravikumar; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Volokh, Michael; Kotresh, Harish Makri Nimbegondi; Shalom, Menny; Thotiyl, Musthafa Ottakam (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: Catalysts; CO2 reduction; O-2 REDUCTION; oxygen reduction